Our first civil war : patriots and loyalists in the American Revolution - Brands, H. W. (Doubleday, 2021)
"New York Times bestselling historian H. W. Brands offers a fresh and riveting narrative of the American Revolution that shows it to be more than a fight against the British, but also a violent battle among neighbors forced to choose sides, Loyalist and Patriot"--